Assessing the impact of the September 11 terrorist attacks on US airline demand - Harumi Ito; Darin Lee (Brown University, Department of Economics, 2003)
This paper assesses the impact of the September 11th terrorist attacks and its after-effects on U.S. airline demand. Using monthly time-series data from 1986-2003, we find that September 11th resulted in both a negative transitory shock of over 30% and an ongoing negative demand shock amounting to roughly 7.4% of pre-September 11th demand. This ongoing demand shock has yet to dissipate (as of November 2003) and cannot be explained by economic, seasonal, or other factors.
Keywords: R41; L16; L93; 330; Airlines; Structural Change; Attenuating Shock; September 11; Politische Gewalt; Luftverkehr; Nachfrage; USA